Norway’s New(s) Wars: Syria in the Norwegian Mass Media - Ottosen, Rune (Nordlit, 2019)
Through two case studies, this article will explore how Norwegian news media framed the Norwegian military presence in Syria. Earlier research by the author has shown how the legal aspects of NATO’s out-of-area operations have been ignored by mainstream media. In this study, emphasis will be put on self-censorship among Norwegian journalists, ignoring the fact that Norwegian special forces took part in military operations inside Syria from May 2017 to March 2018. The hypothesis based on Johan Galtung’s (2002) theory of peace journalism is that mainstream media refused to see the connection between Norway’s bombing of Libya and the escalation of the ‘civil war’ in Syria. According to legal experts, the Norwegian military presence in Syria was a violation of international law, as it supported rebel groups in armed confrontation with the Assad government, recognized by the Norwegian state through diplomatic relations. The hypothesis of the study—based on an explorative investigation of selected Norwegian news media—is that Norwegian politicians, silently supported by the media, have changed basic principles of Norwegian security policy without an open public debate. Before 1999, Norway was a loyal NATO member based on the notion that NATO was a ‘defense alliance’. After the change in NATO strategy to the new out-of-area policy, Norway has in practice become a ‘military tool’ in the geopolitical strategy of the US. This change of policy has, to a large extent, happened without critical investigation by mainstream media. The article presents two case studies of how Norwegian media dealt with the legal issues when Norway was asked to contribute in Syria, and how the Norwegian military presence was reported by Norwegian media in the periods December 2015 to January 2016, as well as May 2017 to March 2018.